Russian Spatial Development Strategy: blind spots in regional specialisations - N. S. Kozyr (Вестник университета, 2022)
The state “Russian Spatial Development Strategy for the period up to 2025” has not only aroused interest in the scientific community, but has also been the object of criticism on the issues of  consistency of the prospective economic specialisations of the constituent entities of the Russian Federation to spatial development objectives. To identify gaps in the content of this strategy, the article compares the economic specialisations of the constituent entities of the Russian Federation with the types of activities described in the “Russian Classification of Economic Activities (OKVED-2) 2021”. The data obtained were compared with the gross value added statistics of the Russian industry structure. The representation of high-tech and knowledge-intensive industries in promising regional economic specialisations was analysed. The results of the study extend the list of criticisms from the Russian scientific community regarding the indicated document. However, a review of foreign studies has shown that the difficulties of strategy development are also inherent in countries with strong planning traditions. An unambiguous conclusion is the need to create a new structure and content document, taking into account the trends in the world and society technological development.